Novel Food legislation and consumer acceptance - importance for the food industry - Knezevic, Nada; Grbavac, Slavka; Palfi, Marina; Sabolović, Marija Badanjak; Brnčić, Suzana Rimac (Emirates Journal of Food and Agriculture, 2021)
Novel foods are defined as food and food ingredients that have not been used to any significant extent in a particular country. This paper offers a brief overview of the current novel food legislation in European Union, Great Britain, USA, Australia and New Zealand, Canada and China. Prior to sale, food business operators (manufacturers or importers) are required, under different regulations and procedures, to submit information to Food Safety Authority about the product in question for a safety assessment. The approaches and specific information used to assess the safety of novel foods are outlined in national Guidelines. Generally, applicant should provide a detailed description of the novel food (identity of the novel food, production process, compositional data, proposed uses and use levels and anticipated intake of the novel food, history of use of the novel food and/or of its source, absorption, distribution, metabolism and excretion, nutritional information, toxicological information and allergenicity) for the safety assessment and market approval of a novel food.